The Peranan Pendidikan Spiritual / Spitiyual Quotient (SQ) Dalam Pendidikan Islam - Fitri, Siska Wahyuni; Wati, Salmi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
Teacher Strategy, Guiding Learning, Broken HomeIn order to educate the nation's life, spiritual intelligence plays a very important role in the world of education because in fact in this life it is not only needed to be intellectually intelligent which is logical, realistic but also requires a spirit of spirit to be divine, that we are well aware that our life is controlling, regulating, and determining, namely Allah SWT, we must also realize that every achievement, and a great achievement because of his will, so that humans are only able to try and beg, pray to Allah SWT which in this case is the implementation of spiritual education in every individual who lives in this world. From the results of the study, there are several conclusions including that there is a very significant difference in conditions before the implementation of spiritual education and after the implementation of spiritual questions education with valid evidence that researchers find there is a change in attitude, namely after routinizing spiritual education both teachers and students become calmer at heart, honest attitude, discipline, increasing day by day. Although there are problems inhibiting the implementation of spiritual quotient education, especially at the beginning of the implementation, namely students are still difficult to manage and so theorder has not been realized properly, over time the solution to the implementation of the orderaccompanied by intensive teacher supervision so that over time children appear their awareness without coercion from anyone to carry out spiritual questions education.